Features of the resources of the hard coal covering in thin coal-seams in Poland - Krowiak, A. (Розробка родовищ, 2013)
The results of analyses of features of geological resources of the hard coal, in majority of mine located in Poland, were presented, according to adopted arbitrarily criteria. All active mines of the hard in the Silesia voivodship were provided with analysis. Результати аналізів особливостей геологічних ресурсів кам'яного вугілля, в більшості шахт Польщі, були представлені згідно довільно прийнятим критеріям. Були проаналізовані всі діючі кам'яновугільні шахти воєводства Сілесія. Результаты анализов особенностей геологических ресурсов каменного угля, в большинстве шахт Польши, были представлены согласно произвольно принятым критериям. Были проанализированы все действующие каменноугольные шахты воеводства Силесия.